2007
DOI: 10.1017/s0022215107007736
|View full text |Cite
|
Sign up to set email alerts
|

Sudden sensorineural hearing loss in a patient with primary antiphospholipid syndrome

Abstract: Consensus exists on the effectiveness of anticoagulant agents in aiding a favourable outcome of sudden sensorineural hearing loss in patients with antiphospholipid syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…10 Autoimmune diseases such as the primary antiphospholipid syndrome also seem to be associated with SSNHL. 11 The endothelium plays a major role in this initial stage of vascular disease. Endothelial dysfunction is characterized by an increased production of cytokines in addition to an elevated expression of adhesion molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Autoimmune diseases such as the primary antiphospholipid syndrome also seem to be associated with SSNHL. 11 The endothelium plays a major role in this initial stage of vascular disease. Endothelial dysfunction is characterized by an increased production of cytokines in addition to an elevated expression of adhesion molecules.…”
mentioning
confidence: 99%
“…Autoimmune diseases such as the primary antiphospholipid syndrome also seem to be associated with SSNHL 11 . The endothelium plays a major role in this initial stage of vascular disease.…”
mentioning
confidence: 99%
“…4–7 SNHL has been linked to APS. 14,16–19 Case reports have indicated a connection between APS and neuronal hearing loss. High antibody titres have been found in patients with unilateral or bilateral SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…reported an association between anticardiolipin antibodies (aCL) and SNHL in a girl with SLE. 14 Since then, SNHL has been linked sporadically to APS, primarily in case reports, 1517 while prospective clinical studies examining SNHL among APS patients are sparse. Moreover, many of the studies addressing the relationship between antiphospholipid antibodies (aPL) and SNHL involved SLE patients and not primary APS patients or examined the prevalence of aPL antibodies per se in patients with SNHL.…”
Section: Introductionmentioning
confidence: 99%
“…An etiology can be identified in only one-third of cases (in decreasing order of frequency: infectious, otologic, traumatic, hematologic, neoplastic), and most SSNHL cases are idiopathic [ 9 ]. The pathophysiological mechanisms underlying the onset of idiopathic SSNHL have been described as viral [ 10 , 11 ], vascular [ 12 , 13 ], pressure-related [ 14 , 15 ], autoimmune [ 16 , 17 ], and genetic [ 18 , 19 ]. It has been reported that examining vestibular organ functions in subjects suffering from SSNHL could help identify its etiopathogenesis [ 20 ].…”
Section: Available Epidemiological Data On Sudden Sensorineural Heari...mentioning
confidence: 99%